JINR participation in the ATLAS physics program - Bednyakov, Vadim A. (Array, 2008)
Summary: Current status of JINR participation in the ATLAS physical program is briefly reviewed. In particular, JINR short- and long-term plans and activities in the ATLAS Higgs, top, SUSY and exotic physics as well as in the standard model physics are discussed